Quantitative differentiation of types of feeding craters of Rangifer tarandus fennicus - Pruitt, Jr., William O. (Rangifer, 1992)
During winter 1983-1984 in the Kainuu region of eastern Finland, based on 1363 api profiles, the Värriö Snow Index (VSI) modelled 3 different types of feeding craters dug by Rangifer tarandus fennicus. When mean log VSI of control sites = < ca. 1.4, the animals used suov'dnji (Lappish) or individual, single-use excavations; when mean log VSI of control sites = > 1.4 < ca. 2.1, the animals used fies'ki (Lappish) or cooperative excavations of the perimeter of a site; when mean log VSI of control sites = > ca. 2.6, the animals switched to using ciegar (Lappish) or linear extensions of a suov'dnji, excavated by a sequence of individuals^iegar-type feeding resulted in reduction of mean log VSI of feeding sites even though VSI of control sites increased. Ciegar-type feeding is interpreted as a successful behavioural adaptation to the Sub-Marginal Period.